Animal behavior for shelter veterinarians and staff - Weiss, Emily; Mohan-Gibbons, Heather; Zawistowski, Stephen (Wiley Blackwell, 2015)
Animal Behavior for Shelter Veterinarians and Staff presents and evaluates the available research and programs that address both animal and human behaviors associated with the intake, management and rehoming of dog and cats. Introductions to dog and cat behavior relevant to any animal professional Reviews behavioral reasons for the relinquishment of dogs and cats Describes intake and assessment protocol, shelter design, training and enrichment programs that reduce stress and enhance behavioral well-being Concepts to improve the adoption process and support the human-animal bond post.- Resumé vydavatel
Keywords: zájmová zvířata -- záchrana; záchranné stanice; chování živočichů; psí útulky; kočky; pets -- rescue; animal behavior; animal rescue stations; dog shelters; cats; elektronické knihy; sborníky; electronic books; papers of several authors